2018
DOI: 10.15740/has/ajss/13.1/45-49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated use of phosphorus, biofertilizers and organic manures on soil available nutrient status and yield of greengram (Vigna radiata L.)

Abstract: The effect of inorganic phosphorus, phosphate solubilising bacteria and vermicompost on yield of greengram and available nutrient status was studied during Kharif 2016 at Agricultural College, Polasa, Jagtial, Telangana state, India. The experiment was conducted with three levels of phosphorus (0, 75 and 100 % RDP), phosphate solubilising bacteria (0 and 2 kg ha -1 ) and vermicompost (0 and 5 t ha -1 ). The results revealed that grain and haulm yields were increased with increasing inorganic P levels and when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Data further revealed that significantly higher yield attributes (number of pods/plant, number of seeds/pod and seed test weight) and yield (seed and stover) were obtained under T 4 (75% of recommended NPK+ seed inoculation by Rhizobium @ 10 g/kg seed + soil application of PSB and KSB each @ 5 kg/ha) treatment over other treatments. Improvement in yield attributes and yield under T 4 treatment was may be attributed to the increased vegetative growth due to effective utilization of nutrients provided by rhizobacteria (N-fixer, P and K solubilizers) and potential production and partitioning of photosynthates as also stated by Kumawat et al (2010) and Bhavya et al (2018 ).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Data further revealed that significantly higher yield attributes (number of pods/plant, number of seeds/pod and seed test weight) and yield (seed and stover) were obtained under T 4 (75% of recommended NPK+ seed inoculation by Rhizobium @ 10 g/kg seed + soil application of PSB and KSB each @ 5 kg/ha) treatment over other treatments. Improvement in yield attributes and yield under T 4 treatment was may be attributed to the increased vegetative growth due to effective utilization of nutrients provided by rhizobacteria (N-fixer, P and K solubilizers) and potential production and partitioning of photosynthates as also stated by Kumawat et al (2010) and Bhavya et al (2018 ).…”
Section: Resultsmentioning
confidence: 60%
“…It also improve the chlorophyll content in plants that regulates the photosynthesis and accumulation of food in plant as stated by (Singh and Sharma 2011). Protein content (22.5%) and yield (238.5 kg/ha) was also found maximum with T 4 (75% of recommended NPK+ seed inoculation by Rhizobium@ 10 g/kg seed + soil application of PSB and KSB each @ 5 kg/ ha) treatment might be due to more N-uptake as suggested by (Bhavya et al 2018).…”
Section: Resultsmentioning
confidence: 77%
“…The amount of soil N, P and K can be important indicators of soil fertility, especially the available nutrients that can be directly absorbed and utilized by plants (Bhavya et al 2018). In all treatments, HF and BW increased the preplant soil AN, AP and AK contents (Fig.…”
Section: Available Nutrient Contentmentioning
confidence: 99%